pH- and temperature-responsive amphiphilic diblock copolymers of 4-vinylpyridine and oligoethyleneglycol methacrylate synthesized by RAFT polymerization - Topuzogullari, Murat; Bulmus, Volga; Dalgakiran, Eray; Dincer, Sevil (ELSEVIER SCI LTD, 2014)
Diblock copolymers of 4-vinylpyridine (4VP) and oligoethyleneglycol methyl ether methacrylate (OEGMA) were synthesized for the first time using RAFT polymerization technique as potential drug delivery systems. Effects of the number of ethylene glycol units in OEGMA, chain length of hydrophobic P4VP block, pH, concentration and temperature on the solution behavior of the copolymers were investigated comprehensively. Copolymer chains formed micelles at pH values higher than 5 whereas unimeric polymers were observed to exist below pH 5, owing to the repulsion between positively charged P4VP blocks. The size of the micelles was dependent on the relative length of blocks, P4VP and POEGMA. Thermo-responsive properties of copolymers were investigated depending on the pH and length of P4VP block. The increase in the length of P4VP block decreased the LCST substantially at pH 7. At pH 3, LCST of copolymers shifted to higher temperatures due to the increased interaction of copolymers with water through positively charged P4VP block. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amphiphilic block copolymers; RAFT polymerization; Stimuli-responsive; BLOCK-COPOLYMER; DRUG; MICELLIZATION; NANOCARRIERS; RELEASE; OXIDE); WATER; ACID; Polymer Science